Social Anxiety Among Bullying Victims: A Case Study on the Role of Assertive Behavior and Self Regulation - Adiawaty, Susi (Sinergi International Journal of Psychology, 2025)
Bullying remains a persistent challenge among adolescents, particularly within Indonesian vocational schools. This study aimed to examine the predictive roles of assertive behavior and self regulation on social anxiety among bullying victims in a vocational high school setting in Makassar. Using a cross sectional correlational design, 127 students were surveyed through validated Likert type scales assessing assertive behavior, self regulation, and social anxiety. Multiple linear regression analysis was performed after confirming the fulfillment of normality, linearity, multicollinearity, and homoscedasticity assumptions. The results indicated that assertive behavior significantly and negatively predicted social anxiety, whereas self regulation did not show a significant independent effect. Together, the predictors explained 8.6% of the variance in social anxiety. Discussion highlighted the critical importance of assertiveness as a protective factor and the potential indirect role of self regulation in adolescents' emotional resilience. Contextual cultural factors, such as hierarchical social norms and limited school resources, were also considered influential in shaping the outcomes. These findings contribute to the growing body of research on bullying, social anxiety, and psychosocial interventions in vocational education contexts. It is recommended that future research explore longitudinal effects and additional moderators to better understand and address social anxiety among adolescent bullying victims.